Case Report: Liver Cysts and SARS-CoV-2: No Evidence of Virus in Cystic Fluid - D'Amico, Francesco Enrico; Glavas, Dajana; Noaro, Giulia; Bassi, Domenico; Boetto, Riccardo; Gringeri, Enrico; De Luca, Maurizio; Cillo, Umberto (Frontiers in Surgery, 2021)
Background: In December 2019 an outbreak of pneumonia, caused by a new type of coronavirus, named severe-acute-respiratory-syndrome-coronavirus-2 (SARS-CoV-2). It quickly spread worldwide, resulting in a pandemic. The clinical manifestations of SARS-CoV-2- range from mild non-specific symptoms to severe pneumonia with organ function damage. In addition, up to 60% of patients have liver impairment or dysfunction, confirmed by several studies by the presence of SARS-CoV in the liver tissue. Methods: we report two cases of symptomatic liver cyst requiring fenestration after recent SARS-CoV-2 infection. Both patients, had hospital admission due to documented SARS-CoV-2 infection. Recently after the infection they developed symptoms caused by an enlarged hepatic cyst: one abdominal pain, the other jaundice. They underwent surgery after two negative swab tests for SARS-CoV-2. Results: Cystic fluid was sent for microbiological test and RT-PCR COVID-19 nucleic-acid assay of the cyst fluid was found to be negative in both cases. Discussion: Although there are not current data that can document a viral contamination of cystic fluid, there are data that document a hepatotropism of COVID-19 virus. Herein we can report that after viral clearance at pharyngeal and nasal swab there is no evidence of viral load in such potential viral reservoir.